Penegakan Hukum Hak Cipta Pada Konser Online Berbayar Yang Diperjualbelikan Kembali Oleh Pengguna Aplikasi - Gabriellea Anya Agatha; Yudho Taruno Muryanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Online paid concerts, which is an Over The Top (OTT) services, are exclusive content that has the potential to be duplicated or distributed commercially by application users. Reselling paid online concerts is a copyright infringement and is still rampant on social media. This indicates that there are problems with the enforcement of copyright law in the field of information and communication technology that are still not effective in preventing infringement and suppressing the pirated content market. This research aims to find out how to enforce copyright law related to OTT services and to examine the problems so that it can be used as a material for national law evaluation. The research method used is normative legal research or library research which is conducted by examining legal library materials consisting of primary and secondary law. The results of this research indicate that the copyright law of OTT services have not been specifically regulated and the government's role in monitoring and eradicating the electronic information piracy market is still not optimal.